Brahmi (Bacopa monnieri): an ayurvedic herb in the management of various diseases - Tamboli, Firoj A; Rangari, Vinod D; Tarlekar, Shreyash D; Jadhav, Rajendra D; Alaskar, Kamal M; Desai, Vaibhava V; Kanthe, Rajesh U (Journal of Postharvest Technology, 2022)
Bacopa monnieri (Scrophulariaceae) is an annual herb, widely distributed throughout the Indian subcontinent. It is known as Brahmi. The whole plant  is extensively used in almost all traditional systems of medicine in India. It is a tiny, slender, succulent herb. The creeping stems that grow leaves and  flowers have nodes that generate roots, and their length ranges from 10 to 30 cmsoft and 1-2 mm thick. The flowers are a light blue or pinkish-white  colour. Triterpenoids, saponins, and bacosides havebeen identified to be this plant's major chemical therapeutic components through various studies.  It has been found that the main element causing therapeutic benefits is bacoside A. It is used as an anti-inflammatory, endocrine, gastrointestinal,  antimicrobial, smooth muscle relaxant effects, analgesic, anticancer, antidiabetic, antifungal, cardiovascular, anti-Ischemic, anti-emetic, anti epilepticand antioxidant but it is best known as a memory enhancer. This review focuses on the phytochemical constituents present in B. monnieri,  its multifarious pharmacological activities, and clinical studies.
Keywords: Bacopa monnieri,; bacosides; bacogenins; bacopasaponins,; multifarious pharmacological activities